Patent Insurance: Towards a More Affordable, Mandatory Scheme? - Fuentes, J. Rodrigo (Science and Technology Law Review, 2009)
Even though businesses insure against myriad risks, patent litigation is often excluded from their general commercial liability insurance policy. Companies understand that patent litigation is an expensive ordeal, and some opt for specialized patent insurance. However, most businesses do not carry such protection because it is too costly. This is unfortunate because some studies suggest that patent insurance fosters research and development among small-to-medium sized enterprises. Following this finding, the European Commission called on CJA Consultants to study the feasibility of a mandatory, EU-wide patent insurance scheme in early 2003. In 2006, CJA Consultants concluded that such a scheme was feasible. This Note analyzes the mandatory patent insurance scheme proposed by CJA Consultants and considers whether a similar scheme could be implemented in the United States. First, the Note provides a background on patent insurance. Then, actual policy specimens from a patent insurer are analyzed to explain the differing types of insurance, their costs, and their shortcomings. Ultimately, the CJA Consultants‘ proposal is analyzed and compared to the identified shortcomings. The Note concludes that a mandatory U.S. patent insurance scheme would fail.